Comparison of radioimmunoassay and fluorescent polarization immunoassay for quantitative determination of vancomycin concentrations in serum. - Ackerman, B H (1983)
A new fluorescent polarization immunoassay (Abbott Laboratories, Diagnostics Division, North Chicago, Ill.) was compared with a standard radioimmunoassay (American Diagnostics Corp., Newport Beach, Calif.) in 34 patients being treated with vancomycin. A total of 123 serum samples were divided and quantitatively analyzed for vancomycin by both assay methods. The results obtained indicated that the two assay methods are comparable (y = 1.01x - 0.81; r = 0.99).